2018
DOI: 10.1016/j.virusres.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Infectivity of okra enation leaf curl virus and the role of its V2 protein in pathogenicity

Abstract: Cotton crop has been severely affected by multiple begomoviruses in Pakistan and India. In our previous study, we found okra enation leaf curl virus (OELCuV), cotton leaf curl Multan betasatellite (CLCuMuB) and cotton leaf curl Multan alphasatellite (CLCuMuA) infecting cotton in Pakistan. The current study was designed to investigate the infectivity of OELCuV and its ability to trans-replicate non-cognate CLCuMuB. Agro-infectious clones containing the partial tandem repeats of OELCuV and CLCuMuB were construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Some reports showed that V2 proteins encoded by some geminiviruses could substantially function in viral pathogenicity [43,55,[57][58][59]. To investigate the role of V2 encoded by TbCSV in virus infection, V2 coding sequence was inserted into and heteroexpressed by potato virus X.…”
Section: The Suppressor Activity Of V2 Is Dispensable For Symptom Aggravation Of Heterogenous Pvx Infectionmentioning
confidence: 99%
“…Some reports showed that V2 proteins encoded by some geminiviruses could substantially function in viral pathogenicity [43,55,[57][58][59]. To investigate the role of V2 encoded by TbCSV in virus infection, V2 coding sequence was inserted into and heteroexpressed by potato virus X.…”
Section: The Suppressor Activity Of V2 Is Dispensable For Symptom Aggravation Of Heterogenous Pvx Infectionmentioning
confidence: 99%
“…Two hydrophobic domains (H1 and H2) and the putative protein kinase C (PKC) phosphorylation motif which have been characterised previously [ 31 , 34 , 35 ] were mapped to this variable N-terminal region ( Fig 1C ). The C-terminal half of V2 contained a CxC motif [ 31 , 33 ] conserved between the two V2 proteins whilst the V2 of V22 also contained three additional C-terminal residues (Gln-Lys-Pro) absent in V30 V2 ( Fig 1C ).…”
Section: Resultsmentioning
confidence: 99%
“…We observed that serine substitution of V2 Thr58 resulted in delayed symptom development. V2 aa positions 58 to 60 constitute the PKC motif which has been reported to have a consensus sequence of Thr-X-Arg, where X is any residue [ 31 , 33 , 35 ]. Alanine substitution of the conserved PKC motif residues previously showed that these residues are required for the subcellular localisation, pathogenicity-enhancing, and RNA silencing suppression activities of several geminivirus V2 proteins [ 34 , 35 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Once the optimal density (OD 600 ) of bacterium was achieved, the bacterial cells were propagated in 10 ml MgCl 2 (10 mM) and acetosyringone (100 mM) incubated at 25-28°C for 3-4 hours before inoculation. The inoculum was subverted into the leaves of N. benthamiana from the underside by using a 5/10 ml needleless injection syringe, as reported earlier ( Saeed et al., 2018 ; Shafiq et al., 2021 ). The inoculated plants were maintained in an insect-free glasshouse with 16/8 hours day/night at 28°C.…”
Section: Methodsmentioning
confidence: 99%